Fiscal decentralization reform in CambodiaS progress over the past decade and opportunities. (Metro Manila, Philippines Asian Development Bank, 2018)
This report reviews Cambodia progress in fiscal decentralization since passing the Law on Administrative Management of the Capital, Provinces, Municipalities, Districts and Khans.This report reviews Cambodia progress in fiscal decentralization since passing the Law on Administrative Management of the Capital, Provinces, Municipalities, Districts and Khans (Organic Law, 2008) and commencing the National Program for Democratic Development, 2010 2019 (which was extended to 2020). Solid progress has been made in providing the architecture for an intergovernmental fiscal transfer system, including recent introduction of the Subnational Investment Fund for which ADB has provided design advisory support and initial capital funding.
Keywords: Cambodia -- Economic policy; Finance, Public -- Cambodia; Cambodia -- Economic conditions; Electronic books